EDUCATION AND EDUCATIONAL SYSTEM MANAGEMENT: STATUS, TRENDS, PROBLEMS AND PROSPECTS - V. P. Panasyuk (Russian State Vocational Pedagogical University, 2017)
Introduction. The current stage of development of education in Russia, characterized by the continuation of reforms and intense innovation processes, require essential changes in management. It takes not only a revision of the paradigmatic foundations of such management, but also the adoption of complex measures for improving its efficiency, and reducing excessive centralization.The aim of the present publication is to study the status and prospects of education management in the Russian Federation.Methodology and research methods. The author used the methodology of an interdisciplinary and system-based approaches to the analysis of the considered phenomenon; methods of theoretical analysis, synthesis and generalization.Results. Negative tendencies and contradictions in modern management of education and educational systems, including problems of differentiation of the rights, competences and powers of bodies of various levels of management are revealed. The condition of education management is considered in the context of common problems of its modernization and key innovative vectors of development of the society. Detailed analysis of paradigmatic foundations of management is carried out; its systemacity and balance are presented from the positions of management members and a specific variety of the functions realized by them. System-genetic foundations of management, its recurrence, compliance with the principles of system inheritance are analysed; effectiveness, equifinality, management efficiency in its social, economic, pedagogical and organizational measurements are studied.Scientific novelty concludes in the reasons identification of a gap between the proper and existing management of an educational system. The perspective directions of improvement of this field are singled out.Practical significance. The author provides the recommendations on the use of the proposed ideas concerning the revision of the current approaches to the management of education and educational systems.